Making Social Knowledge in the Victorian City - Hewitt, Martin, 1962- author.
1 online resource.
Keywords: "This study explores the 'ecology of knowledge' of urban Britain in the Victorian period and seeks to examine the way in which Victorians comprehended the nature of their urban society, through an exploration of the history of Victorian Manchester, and two specific case studies on the fiction of Elizabeth Gaskell and the campaigns for educational extension which emerged out of the city. It argues that crucial to the Victorians' approaches was the 'visiting mode' as particular discursive formation, including its institutional foundations, its characteristic modes and assumptions, and the texts which exemplify it. Recognition of the importance of the visiting mode, it is argued, offers a fundamental challenge to established Foucauldian interpretations of nineteenth century society and culture, and provides an important corrective to recent scholarship of nineteenth century technologies of knowing"--